The Effect of EPS, TATO, CR, PBV on Stock Prices of Energy Companies on the IDX (2021-2024) - Nadia Ratubelia; Fahrul Imam Santoso (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to determine the relationship between Earnings Per Share, Total Asset Turnover, Current Ratio, and Price Book Value on the stock prices of energy sector companies on the Indonesia Stock Exchange over four years, 2021-2024. Earnings Per Share describes a company's ability to generate net profit, Total Asset Turnover indicates the company's efficiency in utilizing its assets, Current Ratio indicates the company's ability to meet short-term liquidity needs, while Price Book Value describes how the market assesses a company's value based on its book value. This study uses a quantitative method with an associative approach. The sample selection method uses a purposive sampling method, by selecting energy sector companies that are continuously listed on the Indonesia Stock Exchange and issue complete financial reports during the study period. The data used are secondary data obtained from annual financial reports and stock price data published on the official website. To analyze the data, the researcher used multiple linear regression with the help of the SPSS program to examine the effect of all independent variables on stock prices. The results show that Earnings Per Share and Price Book Value have a positive and significant effect on stock prices, while Total Asset Turnover and Current Ratio do not have a significant effect. These findings indicate that investors in the energy sector pay more attention to the level of profitability and market value of a company than to the efficiency of assets and the company's liquidity capabilities in making investment decisions.